Additive manufacturing in formula one (F1) cars: A review on processes, applications - BİLİCİ, MUSTAFA KEMAL (My University, 2023)
t Additive manufacturing (AM) technology has been developing rapidly in recent years and its use in different sectors is increasing day by day. The working system of AM technology, unlike traditional production methods, is a layer-based production process by creating layers on top of each other. Due to its advantages such as material savings, low cost, production of parts without the need for molds and design flexibility, especially in complex shaped parts, it has found use in many fields, especially in medical, aviation and automotive. The biggest disadvantage of the AM method is that parts of a certain size can be produced due to the size of the part to be produced. To eliminate this problem in AM technology, it is possible to create large parts by combining small parts. In this research study, the role and development of additive manufacturing in the production and development of Formula One (F1) cars, which is the leading world championship in motor sports, which parts are produced with this method and why, in a system based on continuous improvement, A.M. on what advantages it provides. Examples are given on the parts produced by additive manufacturing in Formula 1 vehicles, and the advantages of being produced with additive manufacturing are explained with sample photographs.
Keywords: Additive manufacturing; formula 1 cars; rapid manufacturing